General Geology and Engineering Geology from KM61 to KM50 Jalan Lojing – Gua Musang, Kelantan - Mohamad Nizu, Nurul Ain (2016)
Jalan Lojing-Gua Musang is traverse the Bentong Raub suture zone which consists of sedimentary rocks and metamorphic rocks. In this project, the author investigated the lithology from KM61 to KM50 of Jalan Lojing-Gua Musang where the rocks consist of quartz mica schist, diamictite and amphibolite schist. However, the occurrence of the formations described by previous researchers are not yet conclusive due to the complexity of the geology in this area. Thus, the detailed geology related to the lithology along this road has been discussed in this project including fracture analysis, thin section analysis and stereographic projection analysis. Furthermore, the geological mapping was produced to provide additional information to the existing geological map. The mapping produced in this project is focusing on the area of study that consists of the three different lithology. Apart from that, an engineering geology investigation especially on the mitigation of slope stability issues that possibly give impact to human and environment is found as important value in this study. From fracture data analysis, it is found that quartz mica schist consist of two sets of discontinuities trending NE direction with maximum stress exerted from NW. The density of discontinuity at diamictite location is obtained at NW direction with one set of discontinuity while the discontinuity of amphibolite schist is trending NE direction. For slope stability analysis, both quartz mica schist and diamictite are stable due to their high peak friction angle of discontinuities which are 48˚ and 65˚ respectively. However, amphibolite schist is in a critical condition of plane failure as the discontinuity is approximately the same as the peak friction angle of the discontinuity plane which is 45˚.